(untitled) (Tabularium Historiae, 2019)
The article describes seven examples of works of art with iconographic links to the medal from 1686. This medal is part of the actions of European monarchs who, with the help of works of art, tried to claim victory over the Turks at the Battle of Vienna. The medal was made by an unknown artist. On the medal, the figure of King Jan III Sobieski is of secondary importance. Analyzing the iconography of the Vienna Battle, it should be noted that there are several examples of works of art showing similarity to the obverse of the 1683 medal. However, depending on the patron, the leading role of this or that monarch was shown. So, for example, assuming that there is a certain relationship between the engraving of The Capture of the Grand Vizier’s Banner (sic!) and the final defeat of the Turks, by Romeyn de Hooghe with the medal from 1683, some important differences can be noticed in the propagation of the artistic vision of the Vienna’s victory by the royal commissioners: Sobieski and probably the Saxon prince Jan Jerzy III. For de Hooghe, who was commissioned by the royal court, the most important thing was to immortalise Jan III Sobieski as the main triumphant of the Turks, but it was not for the author of the medal.